2014
DOI: 10.1136/archdischild-2013-304831
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of primary ciliary dyskinesia

Abstract: Primary ciliary dyskinesia (PCD) is an inherited autosomal-recessive disorder of motile cilia characterised by chronic lung disease, rhinosinusitis, hearing impairment and subfertility. Nasal symptoms and respiratory distress usually start soon after birth, and by adulthood bronchiectasis is invariable. Organ laterality defects, usually situs inversus, occur in ∼50% of cases. The estimated prevalence of PCD is up to ∼1 per 10 000 births, but it is more common in populations where consanguinity is common. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
257
0
19

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(279 citation statements)
references
References 50 publications
3
257
0
19
Order By: Relevance
“…The potential to improve the prognosis of such patients makes the use of WES a very cost-effective strategy in the clinic. 15 …”
Section: Discussionmentioning
confidence: 99%
“…The potential to improve the prognosis of such patients makes the use of WES a very cost-effective strategy in the clinic. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover there is no global agreement regarding the standardisation of conduct or reporting of any of the methods used to diagnose PCD. Diagnosis in Europe is generally based on the following criteria [11,15,17,18]: in a person with a clinical history consistent with PCD confirmation of the diagnosis by at least two of the following methods: (1) "hallmark" high speed videomicroscopy analysis (HVMA), (2) "hallmark" TEM, (3) biallellic disease-causing mutations identified by gene testing, (4) abnormally low nasal nitric oxide (nNO). If HVMA and nNO are the only abnormal tests, these tests should be repeated before making a diagnosis.…”
Section: Diagnosis Of Pcd: State Of the Artmentioning
confidence: 99%
“…Whilst the reason for reduced nNO remains elusive [27], measurement became widely established as a screening test [11,17,19,[28][29][30][31]. A recent meta-A c c e p t e d M a n u s c r i p t analysis of 11 studies comparing nNO during a velum closure breath hold reported a mean nNO output of 19 nl/min (SD 18.6) in PCD (n=478) and 265 nl/min (SD 118.9) in healthy controls (n=338) [32].…”
Section: Page 5 Of 36mentioning
confidence: 99%
See 2 more Smart Citations